Interesting Times for International Humanitarian Law: Challenges from the "War on Terror" - Rona, Gabor (Tufts Archival Research Center, 2005)
Volume 27, Issue 2. Summer/Fall International humanitarian law is fine - as long as it is appreciated for what it is rather than criticized for what it is not. Legal advisor to the International Committee of the Red Cross probes the idea of whether humanitarian law is applicable to the War on Terror and argues that the values of human security and the rule of law enshrined in the Geneva Conventions should be upheld.